Effect of a combined woolwich massage, acupressure, and Breastfeeding Exclusive Self Training (BEST) for moms e-book intervention on ineffective breastfeeding: A case study - Eni Folendra Rosa; Rita Kamalia; Rosdiana Rosdiana; Nelly Rustiati (Lentera Perawat, 2026)
Background: Ineffective breastfeeding may be associated with an inadequate breast milk supply, suboptimal infant latch, breast pain, maternal anxiety, and limited access to understandable breastfeeding information. An approach combining physical stimulation and digital education may provide comprehensive support for mothers experiencing breastfeeding difficulties. Objective: This case study aimed to describe the implementation of a combined Woolwich massage, acupressure, and BEST for MOMS e-book intervention among mothers experiencing ineffective breastfeeding. Methods: A descriptive case study design was employed involving two breastfeeding mothers with infants aged 0–1 month in Sekarjaya Village, East Baturaja District, Indonesia. The intervention was delivered over six visits and comprised breastfeeding education using the BEST for MOMS e-book, demonstration and guided practice of Woolwich massage, and acupressure at the CV17 and ST18 points. Data were collected through maternal nursing assessments, observations of breastfeeding practices and outcomes, procedural checklists, and the Breastfeeding Self-Efficacy Scale–Short Form. The data were analyzed descriptively by comparing each participant’s condition before and after the intervention. Results: Following six visits, both participants demonstrated improvements in breastfeeding status. Infant feeding frequency increased from 5–6 times to more than eight times per day, while urination frequency increased from 4–5 times to eight times per day. Breast milk flow and infant latch also improved. The infants appeared calmer after feeding, whereas maternal breast pain and anxiety decreased. The participant who initially experienced more pronounced breast swelling and pain required a longer period of adaptation. Conclusion: The combination of Woolwich massage, acupressure, and education through the BEST for MOMS e-book may be implemented as a supportive intervention for mothers experiencing ineffective breastfeeding. Studies involving larger samples, comparison groups, and standardized outcome measurements are required to determine the effectiveness of this combined intervention.